Business Sustainability in Southeast Asia: A Systematic Literature Review and Bibliometric Analysis - Febriyantoro, Mohamad Trio (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Business sustainability has become a central concern for organizations navigating the dynamic challenges of today’s economic, environmental, and social landscape. This study explores the evolving dimensions of business sustainability by examining how digital transformation, financial literacy, and entrepreneurial orientation contribute to long-term performance, particularly among micro, small, and medium enterprises (MSMEs) in Southeast Asia. Using a systematic literature review (SLR) approach, 102 Scopus-indexed articles published between 2013 and 2025 were analyzed through PRISMA guidelines. The findings reveal that sustainability is not only driven by internal capabilities—such as innovation, green practices, and employee engagement but also by external forces like stakeholder expectations, digital policy, and post-pandemic recovery demands. Digital tools, when aligned with strong leadership and inclusive governance, are shown to accelerate MSMEs’ ability to adapt and compete sustainably. This research highlights the pressing need for integrated strategies that bridge business resilience with environmental and social value creation. Future studies are encouraged to explore the role of institutional context, cross-country collaboration, and sector-specific innovations to further enrich the discourse on sustainable business growth.